The Extension of the Special Business Mining License (IUPK) under The Law No. 3 of 2020 of the Coal and Mineral Mining: Pro or Cons? - Naila Amatullah; Niki Anane Setyadani; Syarafina Ramadhanty (IHSA Institute, 2020)
The enactment of Law No. 3 of 2020 to amend the Law No. 4 of 2009 of the Coal and Mineral Mining has reaping various controversies lately. One needs to be highlighted from the several issues that were raised in disparately, inter alia, the insertion of provision pertaining to the guarantee of the extension of the KK and PK2PB in the form of IUPK under Article 169 of the New Mining Law. Whereas the former law stipulated that when the contract period has expired the land will be handed over to the State and auctioned, however, the latter law instead “guaranteed” the investors will directly get the aforementioned IUPK. The bizareness of such provision is indeed thought-provoking to be examined from both sides; the government as the regulator and from the people of Indonesia who is ought, constitutionally, to have the utmost prosperity from the exploitation of the natural resources pursuant to principles that needs to be contained therein. Ergo, it is expected that this writing can provide answers in a satisfied manner regarding the fulfillment of philosophical consideration within Article 169 of the New Mining Law.